Pemberdayaan Peserta Didik melalui Pembuatan Custom Bouquet Handicraft guna Meningkatkan Kreativitas dan Keterampilan Kewirausahaan di MA Islamiyah - Siti Maftuhah; Laili Nur Fadlilah; Nofita Rizqi Ramadhani; Alfaini Sabata (Journal of Innovation and Contribution to Community Service, 2026)
Empowering students is a strategic effort to develop their creative potential and entrepreneurial skills from an early age. This community service activity aims to enhance students' creativity and entrepreneurial skills through product creation training. custom bouquet handicraft at MA Islamiyah. The method used is the ABCD approach (Asset-Based Community Development). The program included training, mentoring, and hands-on practice covering design planning, material selection, the manufacturing process, and product marketing strategies. The results of the activities showed that students were able to develop creative ideas in producing bouquets with aesthetic and economic value and demonstrated an increased interest in and understanding of the concept of entrepreneurship. Furthermore, students became more independent, confident, and skilled in managing the products they created. Thus, the empowerment program through the creation of custom bouquets and handicrafts is effective in improving the creativity and entrepreneurial skills of students at MA Islamiyah and has the potential to become an alternative sustainable practice-based learning activity.